The extended mind - Menary, Richard (Cambridge, Mass. : MIT Press, 2010)
Introduction: the extended mind in focus / Richard Menary -- The extended mind / Andy Clark and David J. Chalmers -- Memento's revenge : the extended mind, extended / Andy Clark -- Defending the bounds of cognition / Fred Adams and Ken Aizawa -- Coupling, constitution and the cognitive kind : a reply to Adams and Aizawa / Andy Clark -- The varieties of externalism / Susan Hurley -- The alleged coupling-constitution fallacy and the mature sciences / Don Ross and James Ladyman -- Meaning making and the mind of the externalist / Robert A. Wilson -- Exograms and interdisciplinarity : history, the extended mind, and the civilizing process / John Sutton -- Cognitive integration and the extended mind / Richard Menary -- In defence of extended functionalism / Michael Wheeler -- Consciousness, broadly construed / Mark Rowlands -- The extended infant: utterance-activity and distributed cognition / David Spurrett and Stephen Cowley -- Representation in extended cognitive systems : does the scaffolding of language extend the mind? / Robert D. Rupert -- The extended mind, the concept of belief, and epistemic credit / John Preston.
A Bradford book
Includes bibliographical references and index.
boek